(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
The success of the organization depends on effective recruitment and selection system. Looking at the Kenyan labour market, there are still unfilled vacancies and organisations have problems regarding their staffing. Recruitment by Social Networking Sites is an aspect of a new topic and there is a lack of studies about it. In this study, the main objective is to develop a framework for recruitment and selection process using social networking technologies with a case study on Kenyan universities. The study also focuses its attention to determine how the recruitment and selection practices affect the organizational outcomes. Specifically, it enriches literature by identifying the effect of various social networking sites as recruitment channels. Quantitative research will entail defining specific variables, research questions, as well as using measurements to determine causality. The analysis will be done through inductive methodology to discover the critical elements that emerge during online networking and personal touch, and analysis of factors that affect the selection and use of these technologies. Through this, human resource managers will be able to use the framework for achieving effective recruitment of potential employees through social networking technologies.